Pengaruh Struktur Modal terhadap Pajak Penghasilan Badan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2011-2015 - Nastiti, Vinna Eka Rahmadani; Mintarti, Sri; Setiawati, Ledy (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This research intend to analyze the influence of capital structure that includes: long term debt to assets ratio and debt to equity ratio on corporate income tax. The population in this research are consumer goods industry sector manufacturing companies listed in Indonesia Stock Exchange (IDX) during 2011-2015, as many in 39 companies. The sampling was done by using purposive sampling method and acquired 21 companies as sample. The data were analyzed by using multiple linear regression analysis with SPSS 23.0. The results of this research showed that: (1) long term debt to assets ratio has negative and significant effects on corporate income tax and (2) debt to equity ratio has positive and significant effects on corporate income tax.